PEMANFAATAN TETELAN IKAN TUNA (Thunnus sp.) DALAM PEMBUATAN KECAP IKAN DENGAN PENAMBAHAN ENZIM DAN YOGHURT - Luhulima, Christian F.; Rieuwpassa, Fredrik; Wattimena, Martha L. (INASUA: Jurnal Teknologi Hasil Perikanan, 2024)
Tuna loin is a quarter part of the whole body that is cut lengthwise without bones, skin, and red meat. This products has been the flagship export product of the Maluku province for the past two decades. From the whole tuna, the loin yield is about 39.7%, and the waste is about 60.3% which contain red meat. Red meat is usually sold cheaply and underutilized, while its significantly potential. Fish sauce is a solution for diversifying processed fishery products. This research used the experimental method. The research involves two treatments: 20% salt added with 20% papain enzyme (A1), and 20% salt added with 20% yogurt (A2) on tuna trimmings (Thunnus sp.), with two replications. The results of the organoleptic test assessment showed that fish sauce with 20% salt added with 20% papain enzyme (A1) is the best as it meets the quality requirements of fish sauce according to the Indonesian National Standard for Fish Sauce (SNI. No. 01-4271-1996). As for the objective parameters, treatments A1 and A2 have moisture content of 61.95% and 64.79%, protein content of 2.72% and 2.97%, fat content of 1.97% and 3.82%, ash content of 7.34% and 5.51%, carbohydrate content of 26.02% and 22.91%, and calorie content of 132.69% and 137.9% respectively.